EFFECT OF ANDALIMAN (Zanthoxylum Acanthopodium) NANOHERBAL EXTRACT ADMINISTRATION ON LIVER FUNCTION AND LIVER HISTOPATHOLOGY OF STREPTOZOTOCIN-INDUCED DIABETIC MALE WISTAR RATS - Permata Khaira, Azzuhra; Ginting, Chrismis Novalinda; Chiuman, Linda; Chiuman, Veranyca; Sihombing, Bungaran (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Abstract : Background: Diabetes Mellitus is a systemic disease with hyperglycemia, and can cause Non-Alcoholic Fatty Liver Disease (NAFLD). Nanoherbal of andaliman has an antioxidant effect on the body. Objective: This study aims to determine the effect of nanoherbal of andaliman on liver function and liver histopathology. Method: This study used an experimental method with a post-test-only control group design of 30 male wistar rats induced with streptozosin, divided into 6 groups with nano herbal of andaliman as the testing material. Results: There is no difference in the liver function (SGOT and SGPT) between the groups that are given andaliman and the ones that do not with the p values of 0,183 and 0,449 (p>0,05). There is a difference in liver histopathology between the groups with the p-value of 0,03 (p<0,05), it also shows that the groups that are given andaliman experienced liver degeneration. Conclusion: Nanoherbal of andaliman has the antioxidant effect that acts as hepatoprotection, but also includes some substances that can cause damage to the liver cells. The writer suggested adding more samples, doing the pre-test and post-test examinations, and also analyzing the effect of the steroid and terpenoid in andaliman on the liver cells.